2021
DOI: 10.1186/s12902-021-00785-8
|View full text |Cite
|
Sign up to set email alerts
|

X-linked congenital adrenal hypoplasia: a case presentation

Abstract: Background Most patients with congenital adrenal hypoplasia (AHC) develop symptoms during infantile and juvenile periods, with varying clinical manifestations. AHC is a disease that is easily misdiagnosed as Addison’s disease or congenital adrenal hyperplasia (CAH). There was also a significant time difference between the age at which patients developed symptoms and the age at which they were diagnosed with AHC. Most patients showed early symptoms during infantile and juvenile periods, but were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This dynamic change in adrenal images had never been described before, which also extended the spectrum of characteristics of X‐linked AHC. The previous view was widely held that the atrophy and malfunction of the adrenal resulted from the defective NR0B1 , which affected the development of the adrenal glands (Ouyang et al, 2021 ). Our study suggested that in some X‐linked AHC patients, the destruction of the adrenal glands was likely not to be the finished status but rather a gradual process.…”
Section: Discussionmentioning
confidence: 99%
“…This dynamic change in adrenal images had never been described before, which also extended the spectrum of characteristics of X‐linked AHC. The previous view was widely held that the atrophy and malfunction of the adrenal resulted from the defective NR0B1 , which affected the development of the adrenal glands (Ouyang et al, 2021 ). Our study suggested that in some X‐linked AHC patients, the destruction of the adrenal glands was likely not to be the finished status but rather a gradual process.…”
Section: Discussionmentioning
confidence: 99%